Recent advances in site-specific transgene insertion into the maize genome using recombinases and genome editing endonucleases - Basso, Marcos Fernando; Pinto, Maisa de Siqueira; Nonato, Juliana Vieira Almeida; Dante, Ricardo Augusto; Yassitepe, Juliana Erika de Carvalho Teixeira (Frontiers in Plant Science, 2025)
Random insertion of T-DNA into the maize genome requires the generation of many transgenic events, resulting in high cost and extensive development time. In contrast, site-specific transgene insertion (SSTI) in highly stable genomic regions emerges as an interesting and more viable alternative, as it allows obtaining elite lines in less time and effort. FLP/FRT and CRISPR/Cas9 homology-directed repair (HDR) strategies, as well as their combinations, are currently the most effective for SSTI in maize. The FLP/FRT system still depends on generating a high number of transgenic events, selecting a recombinant target line (RTL), and co-transforming this RTL with a second T-DNA, since there is no prior information on whether the insertion site is considered stable. In turn, CRISPR/Cas9 HDR requires prior information about the insertion site. From this principle, SSTI is effectively targeted by CRISPR/Cas9 HDR, requiring a smaller number of transgenic events. Furthermore, other strategies have been used for SSTI in animal cells and other plant species, and are very promising for establishment in maize as well. Herein, we highlight the importance of SSTI and the advances made in identifying genomic safe harbors in the maize genome. Furthermore, we emphasize the potential of the FLP/FRT system, CRISPR/Cas9 HDR, and CRISPR-associated recombinases and polymerases. We also offer insights into binary and ternary vector strategies, transgene delivery systems, maize tissue culture, and SSTI event genotyping. Finally, we highlight the importance of rigorous quality control for elite lines containing STTI. Therefore, this study provides insights and trends into SSTI in maize mediated by recombinases and genome editing endonucleases.